Application of gain-modulated image intensifier in biomedical imaging - Ho, Jun Hui (2012)
In recent years, the incorporation of image intensifiers into charge-coupled-device (CCD) devices has resulted in intensified CCD (ICCD) systems, which possess high sensitivity in low light conditions, as well as high temporal resolution. Such ICCD systems are typically used in fluorescence applications such as fluorescence lifetime imaging (FLI), but seldom used in the context of diffuse optical tomography (DOT). Thus, this project is focused towards developing novel experimental methods and instrumentation for both DOT and FLI systems, especially with the incorporation of image intensifiers.